Method for assessing basic physical fitness level of water polo players in vertical swimming position - Dopsaj, M.; Manojlovic, N.; Thanopoulos, V. (First international symposium sciences and practices in swimming, 2006)
The assessment of the basic fitness level in the vertical swimming position with the application of a specially developed procedure has been carried out on a sample of 20 members of the national water polo team of Serbia and Montenegro under the age of 20 (WPSCG), and 31 students of the Belgrade Police Academy, as the control group (CONT). The subjects were observed over a course of four training sessions. They were asked to maintain the vertical swimming position with four different weights (termed for the purpose of this research as a minor, medium, major and sub-maximal load) until the full exhaustion. On the basis of raw data for each subject, the function Power-Time has been calculated and subsequently the value of the weight was extracted as a measure of fitness in the vertical swimming position for six different interval values (5, 15, 45, 120, 300 and 600 seconds). The results have showed that on the level of the general linear model difference, all the observed variables between WPSCG and CONT are significantly different - Wilks' Lambda 0.271, Fratio= 63.28, Pvalue=0.000. The largest difference was established in the 300 second interval, i.e. at the aerobic power level Fratio=101.13, WPSCG=13.9±1.7 kg vs. CONT=6.8+2.2 kg.